Nonlinear-elastic strain of underwater pipeline in laying process - Yeliseev, Vladimir Vasilievich; Zinovieva, Tatiana Vladimirovna (Computational Continuum Mechanics, 2012)
The contact problem of laying of an underwater pipeline as a nonlinear-elastic rod is formulated and numerically solved. Influence of various factors, i.e., tension, shear, physical nonlinearity of the material, initial angle and depth, is considered. A new formula for hydrostatic loading is derived and used in calculations. Stresses in the pipe, loading on a vessel, form of the sagging part, and contact pressure are determined.